Empowering Digital Consumers: Legal Literacy Education for Preventing Online Fraud in Indonesia - Purnama, Tri Bayu; Zulham, Zulham; Hidayat, Nurul (Universitas Islam Negeri Sumatera Utara, 2025)
The rise of digitalization has significantly influenced consumer behavior in Indonesia, particularly with the growing popularity of online shopping. However, this shift also exposes consumers to a higher risk of fraud, particularly through misleading and deceptive advertising. This community service initiative was designed to address this issue by raising public awareness and educating online consumers about their legal rights and protections under Indonesian law. A qualitative descriptive method was used, supported by a juridical approach and a literature review of consumer protection laws, including the Indonesian Civil Code, Law No. 8/1999 on Consumer Protection, and the ITE Law. In addition to literature analysis, interviews and public perception surveys were conducted to evaluate the effectiveness of the educational intervention. The findings reveal a significant gap between legal provisions and public understanding, indicating that many consumers are unaware of their rights in digital transactions, making them vulnerable to fraud and misrepresentation. The community service program successfully bridged this knowledge gap by disseminating practical and accessible legal information to the public. The initiative also advocated for the strengthening of regulatory frameworks and encouraged cooperation between government agencies, businesses, and consumers to build a safer digital market environment. In conclusion, improving legal literacy among consumers and promoting proactive regulation are essential to protecting consumer rights in Indonesia’s rapidly growing e-commerce landscape. This program highlights the role of preventive education as a critical component of consumer protection in the digital age, emphasizing the need for multi-stakeholder collaboration and continuous public engagement.